Digital Transformation of Notary Deed Minutes Towards Electronic Format with the Utilization of Blockchain Technology for Efficiency and Security of Data Storage - Mustopa, Mustopa; Herman, KMS (Devotion : Journal of Research and Community Service, 2025)
The development of digital technology has encouraged various sectors to transform, including in the field of notary. One significant change is the transition of notarial deed minutes from physical paper to electronic form. This transformation not only provides efficiency in terms of storage space but also opens up opportunities to improve data security and reliability through the use of blockchain technology. Blockchain, with its decentralized and transparent nature, protects against forgery, loss, or manipulation of data. With the digitization and integration of blockchain-based storage systems, archiving notarial deeds can be more efficient, faster, and safer, and in line with the needs of modernizing legal and administrative systems in the digital era.